Development of spray-dried alginate encapsulated probiotic formulations - Chan, Si Ye (Nanyang Technological University, 2021)
Crosslinked alginate encapsulations have shown promising protective abilities for probiotics against harsh conditions. Spray-drying is a highly efficient process to produce encapsulated probiotic powder. However, there is limited research with regards to the production of in-situ crosslinked alginate formulations via spray-drying. Thus, the objectives of this project were to develop and evaluate spray-dried alginate encapsulated probiotic formulations. Several alginate formulations (alginate, alginate-sucrose, calcium-alginate and calcium-alginate-sucrose) were explored, along with five probiotic strains: Lactobacillus rhamnosus GG, Lactobacillus plantarum wild type, Lactobacillus paracasei NA-G8, Escherichia coli Nissle 1917 and Bifidobacterium longum ATCC15707. Property characterisation of the spray-dried powder was conducted, including tests like exposure to simulated gastric fluid and simulated intestinal fluid, colony-forming units counts of probiotics after spray-drying and storage. LGG, LPWT and L. paracasei encapsulated with the calcium-alginate-sucrose formulation had one of the highest survival rates of more than 10^9 CFU/g after spray-drying and storage at 4 ⁰C for 4 and 8 weeks. A lower survival rate of 10^5 and 10^6 CFU/g after spray-drying was obtained for ECN and B. longum, respectively. LGG and LPWT encapsulated in calcium-alginate-sucrose maintained high survival rates of 10^9 CFU/g after SGF, while L. paracasei experienced a slight drop in the survival rate, obtaining about 10^8 CFU/g. These results highlight the potential of the calcium-alginate-sucrose formulation as an encapsulant material for spray-drying of probiotics. Findings from this project may provide industries with an improved encapsulant formulation to produce spray-dried encapsulated probiotic powder.